A Study on Effectiveness of Communication Skills in English among High-School Students - Ann K.-, Mary; Selvakumar, Y Stanly (Journal of Advanced Research in Humanities and Social Sciences, 2023)
This study dwells in the difficulties of communicating skills in English among High School students. In Chennai, efforts are being taken to improve the use of communication skills among High School students. Since there is a difference between one’s mother tongue and English, students find it difficult to communicate. So many scholars are working in this area to improve the communicating skills of the students. This study also tries to bring out possible solutions to the students to effectively communicate in English. The findings show that there is great difference in the effectiveness of communication skills in English among High School students when it comes to medium of instruction (English/Tamil). Those children who are under the medium of English instruction seem to be able to communicate better than others.